1991
DOI: 10.1002/hc.520020309
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and solution properties of new heterocyclic tellurium compounds based on 5,6‐dimethyl‐1,3‐dihydro‐2‐telluraindene

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
2
8
1
Order By: Relevance
“…It was also found that compound 1 readily reacted with N-bromosuccinimide to form compound 10 (Scheme 1, Table 1). This result agrees well with previous works [4,13]. Compound 1 can be easily oxidized to telluronium salts with alkyl halides such as CH 3 I and C 2 H 5 Br, benzyl bromide, 2,6-dichlorobenzyl bromide, and 4-bromophenacyl bromide to form compounds 5, 6, 7, 8, and 9, respectively, in good yields (Scheme 1).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…It was also found that compound 1 readily reacted with N-bromosuccinimide to form compound 10 (Scheme 1, Table 1). This result agrees well with previous works [4,13]. Compound 1 can be easily oxidized to telluronium salts with alkyl halides such as CH 3 I and C 2 H 5 Br, benzyl bromide, 2,6-dichlorobenzyl bromide, and 4-bromophenacyl bromide to form compounds 5, 6, 7, 8, and 9, respectively, in good yields (Scheme 1).…”
Section: Resultssupporting
confidence: 92%
“…It is worth noting that the reaction of cyanogen bromide with compound 1 unexpectedly gave dibromo derivative 3 instead of di(cyclohexylmethyl)cyanotellurium bromide (Scheme 1). This is in contrast to previously reported works [4,11,12], and suggests that cyanogen bromide can be used as a brominating agent in such reactions. A 13 C NMR spectrum of compound 3, which was prepared by reacting compound 1 with BrCN, did not show a signal corresponding to C O (Table 1).…”
Section: Resultscontrasting
confidence: 83%
See 2 more Smart Citations
“…The large variation for carbon atoms bearing tellurium atoms can be attributed to the polarity of the TeÐC bond. 13,14 Solution polycondensation of 3, 4, and 7 with terephthaloyl chloride and TDI was the general method 15±17 used for the preparation of the new tellurium-containing polyester and polyurethane (Scheme 2). The polymerization reactions were carried out at ambient temperature and as described in our previous work.…”
Section: Resultsmentioning
confidence: 99%